The temperature-dependent ESF of InGaAs well-cluster composite structure - Qingnan Yu; Shuting Yang; Mengjia Chen; Yaxin Wang; Yuxuan Wang; Xinyu Wang; Hongxu Li (AIP Advances)
The InGaAs well-cluster composite (WCC) structure is a special kind of quantum confinement structure formed by indium atom self-fit migration, which has excellent spectral properties. In this paper, an experimental technique for measuring the temperature-dependent emission scaling factor (ESF) is proposed to reveal the luminescence mechanism of the InGaAs WCC structure in more detail. The ESF is derived by collecting the photoluminescence (PL) spectra from the pump regions with different lengths. The ESF has an almost uniform distribution at different temperatures, of which the fluctuation range is ∼7.16 × 1010–3.36 × 1011 W−1 eV−1 s−1. In addition, the ESF with multi-peak characteristics is shown and analyzed according to indium-rich cluster and carrier-injected band-filling rules. It is generated by the multi-component active regions and the special asymmetric band structure caused by indium atom migration. Not only is a new experimental method for measuring ESF proposed in this paper, but also the band-filling rules of InGaAs WCC structures at different temperatures are revealed. This work is significant to promote and develop the new generation of semiconductor lasers with a WCC structure.